Adipocyte SIRT1 controls systemic insulin sensitivity by modulating macrophages in adipose tissue. (7th March 2017) - Hui, Xiaoyan; Zhang, Mingliang; Gu, Ping; Li, Kuai; Gao, Yuan; Wu, Donghai; Wang, Yu; Xu, Aimin
Abstract: Adipose tissue inflammation, characterized by augmented infiltration and altered polarization of macrophages, contributes to insulin resistance and its associated metabolic diseases. The NAD + ‐dependent deacetylase SIRT1 serves as a guardian against metabolic disorders in multiple tissues. To dissect the roles of SIRT1 in adipose tissues, metabolic phenotypes of mice with selective ablation of SIRT1 in adipocytes and myeloid cells were monitored. Compared to myeloid‐specific SIRT1 depletion, mice with adipocyte‐selective deletion of SIRT1 are more susceptible to diet‐induced insulin resistance. The phenotypic changes in adipocyte‐selective SIRT1 knockout mice are associated with an increased number of adipose‐resident macrophages and their polarization toward the pro‐inflammatory M1 subtype. Mechanistically, SIRT1 in adipocytes modulates expression and secretion of several adipokines, including adiponectin, MCP‐1, and interleukin 4, which in turn alters recruitment and polarization of the macrophages in adipose tissues. In adipocytes, SIRT1 deacetylates the transcription factor NFATc1 and thereby enhances the binding of NFATc1 to the Il4 gene promoter. These findings suggest that adipocyte SIRT1 controls systemic glucose homeostasis and insulin sensitivity via the cross talk with adipose‐resident macrophages. Synopsis: The deacetylase SIRT1 protects against metabolic disorders in many tissues. SIRT1 also acts on the transcription factor NFATc1 in adipocytes, thereby enhancing IL‐4 expression. Sirt1 deletion lowers IL‐4 levels, reduces adipose‐resident M2 macrophages, and increases inflammation. Adipocyte‐selective deletion of Sirt1 exacerbates high‐fat diet‐induced insulin resistance and adipose tissue inflammation. SIRT1‐deficient adipocytes cause increased macrophage recruitment and polarization versus pro‐inflammatory M1 subtypes. NFATc1 is deacetylated by SIRT1 and thereby sustains expression of interleukin 4 in adipocytes. Abstract : The deacetylase SIRT1 protects against metabolic disorders in many tissues. SIRT1 also acts on the transcription factor NFATc1 in adipocytes, thereby enhancing IL‐4 expression. Sirt1 deletion lowers IL‐4 levels, reduces adipose‐resident M2 macrophages, and increases inflammation.